Bahasa Indonesia Bahasa Indonesia - Fitrah Izul Falaq; Dedi Kuswandi; Henry Praherdhiono (Jurnal Penelitian Pendidikan IPA, 2023)
The limitation of time, cost, and manpower have been the main problems in facilitating post-training learning. Based on this issue, the research aims to develop a web-based learning platform based on knowledge management system as a learning supplement for independent post-training learning. The development of the application adopted the SECI model which stands for Socialization, Externalization, Combination, and Internalization. The system will record data used as an indicator for making decisions on the material and giving automatic recommendations for each participant. The methodology used in this study is a model proposed by Davidson-Shiver, Rasmussen, dan Lowenthal that consists of Analysis; Evaluation Planning; Concurrent Design which includes design, development, initial implementation, and formative evaluation; Full Implementation; and Summative Evaluation and Research. There are 2 data analysis techniques, qualitative data analysis to measure the accuracy of utilization procedures; and quantitative data analysis to measure technical quality in the form of media validity and learning outcomes. Based on the material expert validation, the material obtained a percentage of 98.75% which is very feasible; media expert validation gained a percentage of 81.25% with a very feasible category; small group trials obtained a percentage of 81.5% in the very feasible category; and product testing obtained a percentage of 87.125%. The results of pre-test and post-test data processing showed an average increase in learning outcomes of 41.53%, with a completeness level of learning outcomes at 90% in the very effective category. As a result, the data inferred that the media is very decent and effective to be used as a supplement for independent post-training learning.